تولي المرأة لمنصب القضاء في ليبيا : دراسة تحليلية مقارنة في الفقه الإسلامي والقانون الليبي - Yousuf, Salih Abdulrahman Alsounusi; Wargadinata, Wildana; Rofiq , Aunur; Haris, Achmad Murtafi (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2025)
This study aims to explore the prevailing view in Libyan society towards women assuming the position of judge, focusing on the opinions and evidence of jurists on this subject, discussing their different points of view, and comparing this with legal legislation in Libya and Islamic jurisprudence. The problem of the research lies in the fact that Libyan society adheres strongly to its traditions and customs, and the problem also arises in the different opinions of jurists on the ruling on women assuming the judiciary in Islam, which prompted the researcher to study the reasons for this difference and divergence in opinions. The researcher relied in his study on a set of research methods: he used the descriptive approach to provide a picture of the issue, and he also used the analytical method to study the data, and used the comparative method to compare different jurisprudential opinions with each other, as well as compare them with legal legislation, in order to reach conclusions about the reasons for the difference. The researcher reached several main conclusions, the most important of which is that the prevailing traditions in Libya reject women taking over the judiciary because of the prevailing culture. In contrast, Libyan law provides that women may hold the judiciary absolutely. In Islamic jurisprudence, jurists have differed in four main directions: the public prohibits women from taking over the judiciary absolutely, while some Shafi'is believe that this is permissible in necessity. As for the Ahnafs, they allow her to judge in matters in which she testifies, while Ibn Jarir al-Tabari and those with him believe that it is permissible for her to assume the judiciary absolutely.